1990
DOI: 10.1128/jvi.64.1.231-238.1990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biological properties of c-mil transducing retroviruses generated during passage of Rous-associated virus type 1 in chicken neuroretina cells

Abstract: IC1, IC2, and IC3 are novel c-mil transducing retroviruses generated during serial passaging of Rous-associated virus type 1 (RAV-1) in chicken embryo neuroretina cells. They were isolated by their ability to induce proliferation of these nondividing cells. IC2 and IC3 were generated during early passages of RAV-1 in neuroretina cells, whereas IC1 was isolated after six consecutive passages of virus supernatants. We sequenced the transduced genes and the mil-RAV-1 junctions of the three viruses. The 5' RAV-1-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Therefore, constitution of 5' ends by a splice process could represent a general mechanism in retrovirus transduction of proto-oncogenes. We previously proposed that a precursor of these early virus forms could be an alternatively spliced U5leader-Ac-onc RNA (9). Obtaining a complete retrovirus requires the acquisition of 3' sequences including a U3 region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, constitution of 5' ends by a splice process could represent a general mechanism in retrovirus transduction of proto-oncogenes. We previously proposed that a precursor of these early virus forms could be an alternatively spliced U5leader-Ac-onc RNA (9). Obtaining a complete retrovirus requires the acquisition of 3' sequences including a U3 region.…”
Section: Discussionmentioning
confidence: 99%
“…IC2 and IC3 were isolated during early passages of RAV-1 on NR cells, whereas ICI was isolated at later passages of culture supernatants during the same experiment. We were able to demonstrate a generation relationship between these earlyand late-passage viruses on the basis of structural analyses of their genomes (9).…”
mentioning
confidence: 97%
“…This experimental cell system also proved useful in establishing a precursor-product relationship between viruses generated successively during milIRmil transduction. Specifically, we showed that late virus forms were generated by further recombination involving sequence homologies between oncogenes and the RAV-1 gag gene (5,6). Therefore, the proposed model may account for the generation of the vast majority of transforming viruses which contain a 5' junction between gag and oncogene exonic sequences (22).…”
Section: L2 Cef Nr2mentioning
confidence: 99%
“…We reported that serial in vitro passaging of Rous-associated virus type 1 , an avian retrovirus that does not carry an oncogene, in chicken embryo neuroretina (NR) cells results in reproducible transduction of the catalytic domain of two related serine/ threonine protein kinases (15,16), c-mil/c-raf (13,14,18) and c-Rmil/B-raf (10). By comparing the genetic organization of several viruses isolated after few or multiple passages of culture supernatants on NR cells, we were able to establish a precursor-product relationship between viruses generated at different stages of transduction (5,6). We showed that the 5' end of early-passage viruses was generated by a splice mechanism between the donor site of RAV-1 leader sequences and acceptor sites of the activated exons.…”
mentioning
confidence: 99%
See 1 more Smart Citation